1992
DOI: 10.1161/01.res.71.5.1123
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ischemia and reperfusion on sarcoplasmic reticulum calcium uptake.

Abstract: To investigate the mechanism underlying postischemic cardiac dysfunction (myocardial stunning), contractility and adenine nucleotide metabolism were studied in three groups of isolated perfused rabbit hearts (control, ischemic, and reperfused), whereas Ca2`uptake by the sarcoplasmic reticulum (SR) was measured in homogenates obtained from them. The hearts were Langendorff-perfused as being the major mechanism underlying postischemic myocardial dysfunction. The hypothesis that a decrease of ATP levels underli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
3

Year Published

1994
1994
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(25 citation statements)
references
References 42 publications
2
20
0
3
Order By: Relevance
“…35 Recovery of the amplitude of Ca 2+ transients was also mainly mediated by restoration of SR Ca 2+ uptake and Ca 2+ stores. 25,26 In the present study, untreated hearts still exhibited a higher diastolic [Ca 2+ ]i early reperfusion. More rapid decline (normalization) of diastolic [Ca 2+ ]i in the KBR-treated heart might also be a consequence of the inhibitory effect of this agent on the NCX.…”
Section: Effects Of the Ncx Inhibitor On [Ca 2+ ]I During Ischemia Ansupporting
confidence: 42%
See 1 more Smart Citation
“…35 Recovery of the amplitude of Ca 2+ transients was also mainly mediated by restoration of SR Ca 2+ uptake and Ca 2+ stores. 25,26 In the present study, untreated hearts still exhibited a higher diastolic [Ca 2+ ]i early reperfusion. More rapid decline (normalization) of diastolic [Ca 2+ ]i in the KBR-treated heart might also be a consequence of the inhibitory effect of this agent on the NCX.…”
Section: Effects Of the Ncx Inhibitor On [Ca 2+ ]I During Ischemia Ansupporting
confidence: 42%
“…Assessment of intracellular Ca 2+ kinetics using rapid caffeine application indicated that reduction of SR Ca 2+ stores occurs during anoxia, 25 and an ischemiainduced reduction of SR Ca 2+ uptake was demonstrated using a biochemical assay. 26 It is unlikely that KBR modified SR dysfunction during ischemia.…”
Section: Effects Of the Ncx Inhibitor On [Ca 2+ ]I During Ischemia Anmentioning
confidence: 99%
“…20) During ischaemia-reperfusion, the deleterious increase in intracellular Ca 2+ concentration appears to result from the reverse operation of the Na + /Ca 2+ exchange mechanism associated with intracellular acidosis and membrane depolarization as well as impaired sarco-endoplasmic reticulum (SR) Ca 2+ -ATPase2 (SERCA2a), which is responsible for SR Ca 2+ uptake. 21,22) Factors that diminish the increase in intracellular Ca 2+ would be expected to attenuate myocardial injury, so downregulation of Ca 2+ channels should be beneficial. Physiologically, the expression of LTCC mRNA was transient decreased soon after myocardial infraction followed by recovery towards normal level in a 4-week follow-up period.…”
Section: Discussionmentioning
confidence: 99%
“…ATPase 2a (SERCA2a), which is primarily responsible for sarcoplasmic reticulum Ca 2+ uptake, was reported to be decreased in protein level or activity in the ischemic myocardium in various animals and humans (4)(5)(6)(7). Additionally, vectormediated gene transfer to increase SERCA2a expression or the use of transgenic animals with SERCA2a overexpression have clearly established the potential beneficial effects in ischemic heart, and thus promoted the field of potential SERCA2a gene therapy in IHD (8)(9)(10)(11).…”
Section: +mentioning
confidence: 99%